ANALISIS PELAYANAN BIDANG FARMASI MENGGUNAKAN INDIKATOR LAYANAN BERBASIS WHO: TINJAUAN SISTEMATIS : Analysis of Pharmaceutical Services Using WHO-Based Service Indicators: A Systematic Review - Yusnita Julyarni Akri (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
Pharmaceutical services in hospitals are an inseparable part of the hospital's health service system that is oriented towards patient service, the provision of quality and affordable pharmaceutical preparations, medical devices, and consumables for all levels of society including clinical pharmacy services. The purpose of this study is to systematically review the implementation of pharmaceutical services based on WHO indicators. The articles used were selected from the Google Scholar journal database published from January 2013 to December 2023. Keywords for the study included "service" or "pharmaceutical" or "pharmacy" or "indicator" or "hospital" or "WHO". A total of 476 articles were generated from the initial search, the author identified 8 articles on pharmaceutical services based on WHO indicators. Based on a systematic review, most hospitals have implemented pharmaceutical services based on WHO indicators. Based on a systematic review, the implementation of pharmaceutical services in accordance with WHO standards is the selection stage: conformity with the hospital formulary; procurement: frequency of procurement of each drug item annually and on an EOQ basis; distribution: the degree of availability of the drug; Usage: percentage of generic prescriptions, percentage of drugs delivered, percentage of drugs labeled complete and average time spent serving prescriptions.